The Effect of Trust, Performance Expectancy, and Mobile Application Quality on Purchase Intention and Purchase Decision: Evidence from Malang City - Imam Rizkika; Edriana Pangestuti; Mohammad Iqbal (Sekolah Pascasarjana Universitas Brawijaya, 2023)
The rapid development of technology has led to various breakthroughs that affect people's lifestyles and behaviour. One of the products of technological advances is the Food Delivery Application (FDA). This study aims to examine the effect of trust, performance expectancy, and mobile application quality on purchase intention and purchase decision among users of the GrabFood in Malang City. This research includes explanatory research with a quantitative approach. The sampling technique used was purposive sampling in order to obtain a total sample of 150 respondents. The analytical method used is SEM-PLS with SmartPLS 4.0 version. The results are that the variables of trust and mobile application quality have a positive and significant effect on purchase intention, but performance expectancy does not have a significant effect on purchase intention. The results of this study also show that the variable purchase intention and mobile application quality have a positive and significant effect on the purchase decision, but trust does not have a significant effect on the purchase decision. The practical implications that can be obtained from the results of this research can be used by GrabFood to evaluate the services and features provided in order to increase consumer purchase intention and purchase decision. Keywords: trust, performance expectancy, quality, purchase intention, purchase decision